Molecular modeling of mercury porosimetry. - Thommes, Matthias; et al. (Studies in Surface Science and Catalysis, 2007)
We review a recently developed mol.-based approach for modeling mercury porosimetry. This approach is built on the use of a lattice model of the porous material microstructure and the use of mean-field d. functional theory (MF-DFT) calcns. and Monte Carlo simulations to calc. the three-dimensional d. distribution in the system. The lattice model exhibits a symmetry between the adsorption/desorption of a wetting fluids and intrusion/extrusion of a nonwetting fluid. In consequence, macroscopic approaches used previously to transform mercury porosimetry curves into gas adsorption isotherms are essentially exact in the context of the model. We illustrate the approach with some sample results for intrusion and extrusion in Vycor and controlled pore glass (CPG). [on SciFinder(R)]
Keywords: mercury porosimetry mol model review